Incorporating the disturbance process of fire into invasive species habitat suitability models - Silverman, Joel, author; Rocca, Monique E., advisor; Laituri, Melinda J., committee member; Martin, Patrick H., committee member (Colorado State University. Libraries, 2008)
This study is motivated by the difficulties land managers face while attempting to simultaneously maintain the natural role of fire in ecosystems and prevent the spread and proliferation of invasive plants. I developed habitat suitability models to predict the responses of three invasive species to fire and other environmental variables: one species in each of three National Parks. For each species, model comparisons tested whether the inclusion of nationally-available data on burn severity, time since fire, and fire occurrence could improve habitat suitability models relative to non-burn data alone. Each species demonstrated significant responses to fire, although incorporation of fire information into the models improved model performance for some species more than for others.
Department Head: Michael J. Manfredo.